Three transition-metal complexes with the macrocyclic ligand meso-5,7,7,12,14,14-hexamethyl-1,4,8,11-tetraazacyclotetradecane (L): [Cu(ClO4)2(L)], [Zn(NO3)2(L)] and [CuCl(L)(H2O)]Cl - Yasmin, S. (2013)
The three transition-metal complexes, (meso-5,7,7,12,14,14-hexa methyl-1,4,8,11-tetra azacyclo tetra decane-κ4 N)bis (perchlorato-κO)copper(II), [Cu(ClO4)2(C18H40N4)], (I), (meso-5,7,7,12,14,14-hexa methyl-1,4,8,11-tetra azacyclo tetra decane-κ4 N)bis (nitrato-κO)zinc(II), [Zn(NO3)2(C18H40N4)], (II), and aqua chlorido (meso-5,7,7,12,14,14-hexa methyl-1,4,8,11-tetraazacyclo tetra decane-κ4 N)copper(II) chloride, [CuCl(C18H40N4)(H2O)]Cl, (III), are described. The mol ecules display a very similarly distorted 4+2 octa hedral environment for the cation [located at an inversion centre in (I) and (II)], defined by the macrocycle N4 group in the equatorial sites and two further ligands in trans-axial positions [two O-ClO3 ligands in (I), two O-NO2 ligands in (II) and one chloride and one aqua ligand in (III)]. The most significant difference in mol ecular shape resides in these axial ligands, the effect of which on the intra- and inter molecular hydrogen bonding is discussed. In the case of (I), all strong hydrogen-bond donors are saturated in intra molecular inter actions, while weak inter molecular C - H⋯O contacts result in a three-dimensional network. In (II) and (III), instead, there are N - H and O - H donors left over for inter molecular inter actions, giving rise to the formation of strongly linked but weakly inter acting chains. © 2013 International Union of Crystallography.